Australia's refugee policy: domestic politics and diplomatic consequences. Issue 6 (1st November 2016) - Maley, William
ABSTRACT: Refugee policy involves a two-level game. For Australia since approximately 1998, the politics of refugees has been toxically affected by domestic politics. This has had potentially negative effects on Australia's reputation and soft power. This article provides an overview of the issue, explores the ways in which considerations of domestic politics have come increasingly to shape Australia's policy and concludes with a discussion of the consequences of Australia's treatment of refugees for its diplomacy and soft power.